2016
DOI: 10.1021/acs.jmedchem.6b01156
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of [5-Amino-1-(2-methyl-3H-benzimidazol-5-yl)pyrazol-4-yl]-(1H-indol-2-yl)methanone (CH5183284/Debio 1347), An Orally Available and Selective Fibroblast Growth Factor Receptor (FGFR) Inhibitor

Abstract: The fibroblast growth factor receptor (FGFR) family of receptor tyrosine kinases regulates multiple biological processes, such as cell proliferation, migration, apoptosis, and differentiation. Various genetic alterations that drive activation of the receptors and the pathway are associated with tumor growth and survival; therefore, the FGFR family represents an attractive therapeutic target for treating cancer. Here, we report the discovery and the pharmacological profiles of 8 (CH5183284/Debio 1347), an orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Currently, several FGFR-selective inhibitors, such as AZD4547 (11), NVP-BGJ398 (12), and Debio 1347/CH5183284 (13,14), are being used in clinical trials with patients who have FGFR genetic alterations in several tumor types. In one study for gastric cancer, AZD4547 demonstrated promising efficacy in patients harboring FGFR2 amplification (15), with three out of six FGFR2amplified patients obtaining partial response on AZD4547 monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several FGFR-selective inhibitors, such as AZD4547 (11), NVP-BGJ398 (12), and Debio 1347/CH5183284 (13,14), are being used in clinical trials with patients who have FGFR genetic alterations in several tumor types. In one study for gastric cancer, AZD4547 demonstrated promising efficacy in patients harboring FGFR2 amplification (15), with three out of six FGFR2amplified patients obtaining partial response on AZD4547 monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…After the 3D structure of the FGFR protein was reported, it was easier to design selective and potent inhibitors-targeting the FGFR. Numerous representative inhibitors exist, including AZD4547 15 , NVP-BGJ398 16 , CH5183284 17 , LY2874455 18 and JNJ-42756493 19 ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, aberrant signaling of FGF/FGFR has been frequently found in various cancers, making FGFR a hot therapeutic target in anticancer drug development [ 11 ]. Selective and potent FGFR inhibitors are needed, because, in general, compounds that are selective to one intended target kinase can potentially claim a more favorable safety profile than multi-target compounds [ 12 , 13 , 14 ]. Currently, several FGFR-targeted small molecules have been evaluated in clinical trials for cancer treatment, such as NVP-BGJ398 ( 1 ) [ 15 ], AZD4547 ( 2 ) [ 16 , 17 ], LY2874455 ( 3 ) [ 18 ], and CH5183284 ( 4 ) [ 19 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%